Reproductive biology of the blue swimming crab Portunus pelagicus (Linneaus, 1758) in Sibuyan sea, Philippines. - Parrenas, Judy Angela Carmela Roxas
The blue swimming crab Portunus pelagicus is considered to be one of the most commercially imported crab species in the world. This study generaaly aims to determine and describe the reproductive biology of Portunus pelagicus collected from Sibuyan Sea, Philippines using macroscopic and microscopic techniques. In the collection sites of Barra and Punta Cogon, Roxas City, Capiz, Philippines, 30 crabs samples per month from December 2016 to May 2017 were sexed, and measured in terms of body weight (g) and carapace width (CW). Ten out of 30 crabs were dissected for the determination of the different gonad stages both for males and females through morphological and historical examinations. Other important aspects of reproductive biology that were analyzed include the size at sexual maturity, monthly percent occurrence of each gonad stages of males and females as well as the monthly occurrence of both sexes, gonadosomatic index (GSI) and gonad index (GI). Four gonad stages were characterized for females, while there were 3 for males. The female gonad maturation stages are immature (stage I), early maturing (stage II), late maturing (stage III) and mature (stage IV). For males, the three gonad stages are immature (stage I), maturing (stage II), and mature (stage III). Size of sexually mature females ranged from 100.5 ? 135 mm CW, while 102.1 ? 149 mm CW for males. Peak of females in mature stage was in April, while mature males were present throughout the sampling months except in February. GSI and GI are directly proportional to the occurrence of males or females having mature gonads. The information gathered in the present study will be beneficial for the conservation and management as well as sustainability of the catch of the blue crabs in the fishing areas.